Pengembangan Lembar Kerja Peserta Didik (LKPD) Bermuatan STEM pada Materi Energi Kelas IV Sekolah Dasar - Anita Anita; Siti Nur Asmah; Muhammad Aqmal Nurcahyo (Edukhasi: Jurnal Inovasi Pendidikan, 2023)
LKPD containing STEM methods is applied to grade IV elementary schools in delivering material about energy which involves many events that exist in the real world everyday. Students will be taught the technique of creating a simple tool related to energy matter, then apply various existing technologies in explaining energy matter. The description above attracts researchers to develop teaching materials about STEM-laden LKPD through R&D research. This research is a type of R&D (Research and Development) or development which is interpreted as a research conducted by creating a product and then testing its effectiveness. Based on the validation of material experts, design experts and linguists. The development of STEM-charged LKPD on energy materials at SDN 41 Sungai Raya can be categorized as feasible. This feasibility is obtained from expert validators, both linguists, design, and material experts. Overall, the feasibility aspect of the material obtained a score of 76% in the "Good" category. Overall, the feasibility aspect of the design obtained a score of 82% in the "Very Good" category. Overall, the language feasibility aspect obtained a score of 86% in the "Very Good" category. Small and large group trials have a score of 100 and have the criteria of "Very Practical" so that it can be said that STEM-loaded LKPD teaching materials on the material always save energy, are very practical and pass the trial